Mitigating abiotic stress in citrus: the role of silicon for enhanced productivity and quality - de Souza Junior, Jonas Pereira (2025)
The intensification of global warming has exacerbated abiotic stresses in citrus production, posing significant threats to both fruit yield and quality. Stressors such as drought, extreme temperatures, and salinity disrupt key physiological and biochemical pathways, thus impairing nutrient assimilation, inducing oxidative stress, and affecting fruit development. As climate change continues to amplify these challenges, sustainable mitigation strategies are needed for enhancing citrus resilience. This review explores the multiple effects of abiotic stress on citrus trees and evaluates the role of silicon (Si) as a promising ameliorating agent. Silicon has been increasingly recognized for its capacity to mitigate stress-induced damage through mechanisms such as enhanced photosynthetic efficiency, improved water-use efficiency, upregulated antioxidant defense systems, improved cell wall integrity, and modulation of stress-responsive gene expression. Moreover, Si contributes to maintaining fruit quality by stabilizing biochemical parameters such as sugar concentration, acidity balance, and bioactive compound retention. Despite growing evidence supporting the protective functions of Si, further research is required to optimize its practical application in commercial citrus production. Future studies should focus on elucidating the molecular and physiological pathways underlying Si-mediated stress tolerance and developing targeted Si fertilization suited for varying environmental conditions. Harnessing the potential of Si offers a viable strategy to enhance citrus tree productivity, improve fruit quality, and ensure long-term agricultural sustainability in a changing climate.